Bus services: governance in five Malaysian states - Ponrohono, Zakiah; Bachok, Syahriah; Mohamed Osman, Mariana; Ibrahim, Mansor (IIUM Press, 2015)
The chapter explain on the literature review on the governance of bus services in five states in Malaysia